Electron Spin Resonance of Chlorophyll and the Origin of Signal I in Photosynthesis - Norris, J. R. (1971)
A comparison has been made between Signal I, the photo-electron spin resonance signal associated with the primary light conversion act in photosynthesis, and free-radical signals generated in various chlorophyll species in vitro. The esr signals obtained from chlorophyll·monomer, (Chl·L)(+.), chlorophyll dimer, (Chl(2))(+.), and chlorophyll oligomer, (Chl(2))(n)(+.), are broader than Signal I, whereas the chlorophyll-water adduct, (Chl·H(2)O)(n)(+.), gives a signal very much narrower than Signal I. The unusually narrow signal from (Chl·H(2)O)(n)(+.) has been ascribed to spin migration, or to unpaired spin delocalization over a large number of chlorophyll molecules. The linewidth of Signal I can be accounted for by a similar delocalization process. A theoretical relationship between the esr linewidth and the number of chlorophyll molecules, N, over which an unpaired spin is delocalized, takes the form ΔH(N) = 1/√N·ΔH(M), where ΔH(M) is the linewidth of monomer (Chl·L)(+.). This relationship for N = 2 accounts well for the linewidths of Signal I in green algae, blue-green algae, and photosynthetic bacteria in both the (1)H- and (2)H-forms. The linewidth of Signal I (as well as the optical properties of reaction-center chlorophyll) are consistent with unpaired spin delocalization over an entity containing two chlorophyll molecules, (Chl·H(2)O·Chl)(+.).